A multichannel system integrating molecularly imprinted conductive polymers for ultrasensitive voltammetric determination of four steroid hormones in urine - Lee, Mei-Hwa; Thomas, James L.; Liu, Wei-Chiun; Zhang, Zheng-Xiang; Liu, Bin-Da; Yang, Chien-Hsin; Lin, Hung-Yin (Mikrochimica acta (1966), 2019)
This work reports on a modularized electrochemical method for the determination of the hormones cortisol, progesterone, testosterone and 17β-estradiol in urine. These hormones were employed as templates when generating molecular imprints from aniline and metanilic acid by electropolymerization on the surface of screen-printed electrodes. The electrically conductive imprint was characterized by SEM, AFM and cyclic voltammetry. A four-channel system was then established to enable simultaneous determination of the hormones by cyclic voltammetry. The detection limits for cortisol, progesterone, testosterone and 17β-estradiol are as low as 2, 2.5, 10 and 9 ag·mL −1 (for S/ N = 3). Graphical abstract A four-channel system was established to enable simultaneous determination of 4 steroid hormones by cyclic voltammetry and by using moleculalry imprinted polymers.